Maximum Sprite Streamer Luminosity Near the Stratopause. Issue 21 (11th November 2019) - Füllekrug, Martin; Nnadih, Stanislaus; Soula, Serge; Mlynarczyk, Janusz; Stock, Micheal; Lapierre, Jeff; Kosch, Michael
Abstract: Sprites are composed of numerous streamers which exhibit transient luminosities in the upper middle atmosphere above thunderclouds after initiation by an intense positive lightning discharge, often followed by lightning continuing current. Here we report the discovery of a sprite which exhibits its main luminosity near the stratopause. This novel phenomenon is attributed to a sudden surge of intracloud lightning leader activity, based on a rigorous analysis of our observed electromagnetic waveforms. Each lightning leader discharge causes an additional electric field that generates a small amount of electromagnetic energy near the stratopause and thereby contributes to the overall sprite luminosity morphology. The observation of sprite streamers near the stratopause is important because it is relevant for the ongoing assessment of the lightning impact on N2 and CO2 with emissions from the near to far infrared part of the spectrum. Key Points: Maximum sprite streamer luminosity near stratopause detected Sprite morphology attributed to surge of intracloud lightning activity